Cross-Cultural Communication Strategy of Kristal Hotel Management in Adapting to the Cultural Shock of Expatriates as Customers of Satu Lagi Bar - Lena, Pratika Martha; Alifahmi, Hifni (Eastasouth Institute, 2025)
The aim of this research is to analyze the cross-cultural communication strategy employed by the Hotel Kristal Jakarta management in managing the cultural shock phenomenon among regular expatriate customers of Satu Lagi Bar. Employing a qualitative descriptive approach, data were collected using in-depth interviews, observation, and documentation from expatriates, hotel staff, and hotel management representatives. The study employs Edward T. Hall's High-Context and Low-Context Cultures theoretical notion, Berry's Acculturation Strategy, as well as the W-Curve Model of cultural adaptation. The findings reveal that Hotel Kristal's management has formulated three key strategies: (1) staff cultural sensitivity training to develop intercultural awareness and communication competence; (2) staff communication strategies—verbal and non-verbal—employed to successfully communicate with expatriates; and (3) creation of a Third Culture Space at Satu Lagi Bar where foreign and local communities' values are reconciled. With these approaches, cultural shock in expatriates was significantly reduced, leading to easier social adjustment, emotional ease, and long-term customer loyalty. The study asserts that Hotel Kristal's cross-cultural communication approach is successful because it manages to make the bar a point of social integration where inclusiveness and intercultural sensitivity are possible within a multicultural hospitality environment.